History Of The Development Of Islamic Dakwah In Spreading Islamic Teachings - Moh. Alam Sugandi; Abdul Aziz Romdhoni (Penerbit Hellow Pustaka, 2023)
Islamic Da'wah is an Islamic communication activity, Da'wah is a communication tool in disseminating Islamic teachings. Allah SWT has prepared devices that make it possible to communicate. The de vice is the tongue and all its supports such as hearing, sight and heart. The development of Islamic Da'wah cannot be separated from the role of the Prophet Muhammad SAW in spreading Islamic teachings during difficult times, such as when the Prophet Muhammad was just spreading Islamic teachings in secret because at that time humans were in the period of ignorance and it was still difficult to believe in new teachings. brought by the Prophet. However, when there were already many followers, the Prophet Muhammad spread the teachings of Islam openly. So this is an important event in communication in Islam.